HUBUNGAN ANTARA PEMBERIAN MAKANAN TAMBAHAN PADA USIA DINI DENGAN TINGKAT KUNJUNGAN KE PELAYANAN KESEHATAN DI KELURAHAN SINE SRAGEN - Murniningsih, Murniningsih; Sulastri, Sulastri (Jurnal Berita Ilmu Keperawatan, 2008)
Background. A mother who has generally to give an increasing food before a baby has 6 month old, there is difficult to understand a new feed method which it’s more healthy. While this fact can annoyance the healthy of baby and the frequentations of visiting to the healthy servant is often more. Objective. This research to tendency to know a relation an increasing feeding at younger old with phase of visiting to healthy servant. Methods. Type of the research is observational of research which us a correlation kind for looking a condition objectively. The research has done in Sine Sragen with taking sample to 48 of baby at 6-12 months old. A total sampling method was used to take and interview. The data, then, was analyzed by using a nonparametric statistic, a bivariate technique, namely, with correlation analysis of Rank Spearman. Conclusions. Results of the research indicated that: (1) Increasing feed method for a baby at 6-12 months old in Sine Sragen that base done the research results is look in that an increasing feed except ASI was gift although the age of baby is not 6 month complete and there is often gift although a baby was suckled. (2) A baby with 6-12 months old in Sine is often visited to the healthy servant. A visiting to the healthy servant at is come in to often category that is 26 person, and than precisely category is 18 person, and rarely category is 4 person. High frequentation of visiting to the healthy servant because an often of the children have a diseases like diarrhea, allergic, or difficult to defecate. (3) From bivariate analysis with correlation equation, a correlation coefficient value of 0,575 was obtained with tcalculation > ttable (6,832 > 2,042) at significance level of 5%. It’s mean there is a positive relation that significance between an increasing feed at younger old with the level of visiting to the healthy servant. An increasing feeding that so early will make a healthy disturbing to the baby in other day.